Human Dimensions and Visitors’ Perspective in Freshwater Crayfish Conservation: The Case of a Protected Area in Italy - Elena Mercugliano; Valeria Messina; Marco Bonelli; Raoul Manenti; Davide Scaccini; Linda Ferrante; Pierfrancesco Biasetti; Barbara de Mori (Diversity, 2023)
Human dimensions in endangered species conservation are often overlooked. However, including human dimensions in conservation projects can help conservationists integrate social and ecological dimensions and investigate individual or society’s perspectives toward conservation efforts. The aim of this study was to investigate how visitors of a protected area perceived the conservation of the native white-clawed crayfish (Austropotamobius pallipes), a species recently brought to disappearance by the introduction of the spiny-cheek crayfish (Faxonius limosus). From August to October 2017, we distributed a questionnaire to park visitors, aiming to: (i) identify behaviors that could affect the conservation of the native crayfish after reintroduction; (ii) investigate if visitors’ awareness and knowledge of native freshwater crayfish may increase approval for conservation initiatives. Of the 290 respondents, most (73%) had never heard of alien species. The respondents’ inclination to be favorable to resource investment and alien crayfish eradication and to perform specific educational training was significantly related to their knowledge of crayfish features. Knowledge of freshwater crayfish features resulted in being a main determinant in affecting visitors’ attitudes towards conservation initiatives. These results confirm that visitors’ awareness can increase approval for conservation programs and the importance of investigating the proper human dimensions before establishing management actions for endangered species.